History/Histoire e Digital Humanities La nascita della storiografia letteraria italiana fuori d'Italia - Rebora, Simone (Biblioteca di Studi di Filologia Moderna, 2018)
This volume reconstructs the birth and evolution of the Italian literary history in France and England during the 19th century. In the French context, a comparative reading of the works by Pierre-Louis Ginguené and Jean Charles Léonard Simonde de Sismondi confirms that the subject had already reached its maturity at the beginning of the century. On the other hand, in England, the path leading from Ugo Foscolo to John Addington Symonds passes through multiple genres and sources, including collections of biographies, anthologies of translations, travel books, histories of individual literary genres, histories from the Middle Ages and the Renaissance. At the end of this path, a software pipeline is tested and developed with the aim of expanding the analysis through the computational tools of the Digital Humanities.